A Role of an Edge Computing Technologies for the Internet of Things in Smart Cities - et. al., R. Deepa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Data-thorough analysis is the biggest contest in smart cities, due to the ubiquity of different types of devices, with the number of device explosions and the numeral of Internet of Things (IoT) rest area attached to smart cities. Using shrewd computing technology to create critical infrastructure and services for the city - including city administration, education, health, public safety, land, shipping and services - is smarter, more connected and efficient. In this paper, we explore the important technologies and structures already built in the literature to identify the right people for inclusion in smart cities for computing development.